Effect of Kaempferia parviflora Wall. ex. Baker on sexual activity of male rats and its toxicity. - Sudwan P. (2014)
Kaempferia parviflora Wall. Ex. Baker (Krachaidum) has long been used among Thai men for sexual enhancement. The aim of this study was to determine the effect of K. parviflora ethanolic extract on the sexual behavior of male rats and its toxicity. The experiment was divided into three groups of rats given K. parviflora extract at doses of 60, 120, and 240 mg/kg BW for 60 days, whilst a control group received distilled water at 1 ml/day per oral. The results showed that all groups of male rats had significantly higher courtship behavior during the first 10-minute period of observation than in the 2nd and 3rd 10-minute periods, except those receiving the highest dose of K. parviflora. They revealed the same amount of courtship behavior throughout a whole 30-minute period, which was significantly lower than the control group. There was no significant difference between treated and control groups in other sexual behaviors; mount frequency (MF), intromission frequency (IF), mount latency (ML), or intromission latency (IL). Toxicological study revealed no significant difference of hemoglobin, WBC or differential cell count. All dosages had no effect on kidney and liver function, according to the normal values of blood urea nitrogen (BUN), creatinine (Crea), aspartate aminotransferase (AST) and alanine aminotransferase (ALT). Nevertheless, the histopathological study showed a morphological change in the liver. It was concluded that K. parviflora extract at 240 mg/kg BW reduced the time in the first 10 mintues of rat courtship behavior and the use of high and chronic doses of K. parviflora in humans should be considered inadvisable.